Genome-Wide Identification, Evolution and Expression Analysis of the Glutathione S-Transferase Supergene Family in Euphorbiaceae - Duan, Qiang; Li, Guo-Rui; Qu, Yi-Peng; Yin, Dong-Xue; Zhang, Chun-Ling; Chen, Yong-Sheng (Frontiers in Plant Science, 2022)
Euphorbiaceae, a family of plants mainly grown in the tropics and subtropics, is also widely distributed all over the world and is well known for being rich in rubber, oil, medicinal materials, starch, wood and other economically important plant products. Glutathione S-transferases constitute a family of proteins encoded by a large supergene family and are present widely in animals, bacteria, fungi and plants, but with few reports of them in Euphorbiaceae plants. These proteins participate in and regulate the detoxification and oxidative stress response of heterogeneous organisms, resistance to stress, growth and development, signal transduction and other related processes. In this study, we identified and analyzed the whole genomes of four species of Euphorbiaceae, namely Ricinus communis, Jatropha curcas, Hevea brasiliensis and Manihot esculenta, which have high economic and practical value. A total of 244 GST genes were identified in them. Based on their sequence characteristics and conserved domain types, the GST supergene family in Euphorbiaceae was classified into 10 subfamilies. The GST supergene families of Euphorbiaceae and Arabidopsis have been found to be highly conserved in evolution, and tandem repeats and translocations in these genes have made the greatest contributions to gene amplification here and have experienced strong purification selection. An evolutionary analysis showed that Euphorbiaceae GST genes have also evolved into new subtribes (GSTO, EF1BG, MAPEG), which may play a specific role in Euphorbiaceae. An analysis of expression patterns of the GST supergene family in Euphorbiaceae revealed the functions of these GSTs in different tissues, including resistance to stress and participation in herbicide detoxification. In addition, an interaction analysis was performed to determine the GST gene regulatory mechanism. The results of this study have laid a foundation for further analysis of the functions of the GST supergene family in Euphorbiaceae, especially in stress and herbicide detoxification. The results have also provided new ideas for the study of the regulatory mechanism of the GST supergene family, and have provided a reference for follow-up genetics and breeding work.